Dissecting Cultural Transition: A Deep Dive into Chinua Achebe’s Things Fall Apart - M G, Sangeetha (International Journal of Environment, Agriculture and Biotechnology, 2023)
This study explores the profound narrative layers within Chinua Achebe's seminal work, Things Fall Apart, shedding light on the intricate dynamics of pre- and post-colonial Igbo society. Through a meticulous examination of the vibrant setting of Umuofia, the analysis uncovers the rich cultural tapestry depicted in the novel and its subsequent transformation under colonial influence. The paper seeks to foster a nuanced understanding of African history, urging readers to acknowledge the complex interplay of traditions and values that define the African heritage, thus challenging single narratives and reshaping public perception of a historically vibrant and multifaceted continent.